Evolutionary characteristics of corporate environmental governance policies in China: a policy instrument analysis (1982–2023) - Tian, Zehua; Yang, Wusong; Tang, Xi (Frontiers in Environmental Science, 2025)
Corporate environmental governance has emerged as a critical global priority amid escalating environmental challenges. In recent years, many countries have implemented laws such as “Supply Chain Laws” and “Corporate Due Diligence Laws” to strengthen corporate environmental accountability. In China, the introduction of the Administrative Measures for the Legal Disclosure of Corporate Environmental Information in 2021 marked a significant shift toward mandatory corporate environmental governance. This study traces the evolution of China’s corporate environmental governance policies through a policy text analysis of 140 documents issued by the central government between 1982 and 2023. The analysis identifies three distinct developmental stages: (1) the pollution control phase (1982–2006), characterized by command-and-control measures; (2) the social responsibility advocacy phase (2007–2020), emphasizing voluntary and market-based mechanisms; and (3) the mandatory environmental obligations phase (2021–present), introducing stricter regulatory requirements. While the current framework reflects principles of collaborative governance, significant challenges remain, including weak communication channels, free-rider problems, and limited extraterritorial application of environmental policies. This study provides a comprehensive analysis of China’s corporate environmental governance policies, offering insights and actionable recommendations to enhance their effectiveness and contribute to global discussions on sustainable corporate governance.